2015
DOI: 10.1016/j.ibmb.2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

The CPCFC cuticular protein family: Anatomical and cuticular locations in Anopheles gambiae and distribution throughout Pancrustacea

Abstract: Arthropod cuticles have, in addition to chitin, many structural proteins belonging to diverse families. Information is sparse about how these different cuticular proteins contribute to the cuticle. Most cuticular proteins lack cysteine with the exception of two families (CPAP1 and CPAP3), recently described, and the one other that we now report on that has a motif of 16 amino acids first identified in a protein, Bc-NCP1, from the cuticle of nymphs of the cockroach, Blaberus craniifer (Jensen et al., 1997). Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 23 publications
0
36
0
Order By: Relevance
“…Despite its limitations, He et al (2007) confirmed the authenticity of many of the CPs we had annotated and provided us with additional members of known CP families and several new families of CPs. Since then, three previously unrecognized families of CPs have been reported: CPAP1 and CPAP3 (Jasrapuria et al, 2010; Tetreau et al, 2015) and CPCFC (Vannini et al, 2015). Further annotation based on these results and a far more robust proteome (Vector Base AgamP4.2) resulted in a cuticulome of An.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite its limitations, He et al (2007) confirmed the authenticity of many of the CPs we had annotated and provided us with additional members of known CP families and several new families of CPs. Since then, three previously unrecognized families of CPs have been reported: CPAP1 and CPAP3 (Jasrapuria et al, 2010; Tetreau et al, 2015) and CPCFC (Vannini et al, 2015). Further annotation based on these results and a far more robust proteome (Vector Base AgamP4.2) resulted in a cuticulome of An.…”
Section: Introductionmentioning
confidence: 99%
“…These genes code for only 282 distinct CPs, because the protein products of several genes are identical. The CP genes have been classified into 13 distinct families and some orphans (Willis, 2010; Willis et al, 2012; Ioannidou et al, 2014; Tetreau et al, 2015; Vannini et al, 2015). This information is summarized in Table 1 and all CP sequences where we identified peptides in this study are in Supplementary File 1.…”
Section: Introductionmentioning
confidence: 99%
“…Sixteen of the 19 primary antibodies tested in this study were used in previous studies by Vannini et al (2014b; 2015) and Vannini and Willis (2016). All the antibodies, except for the anti-3RC Cluster and anti-CPCFC1, were raised against synthetic peptides at Genscript Inc. (Piscataway, NJ) and affinity purified.…”
Section: Methodsmentioning
confidence: 99%
“…In attempts to learn why there are so many CPs, we have examined the precise location of a small number of these proteins within the cuticle with EM immunolocalization (Vannini et al, 2014b, 2015; Vannini and Willis, 2016). The structures we examined had long stretches of seemingly identical cuticle and the epitopes detected for individual CPs covered large areas of these structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation